L-shaped association between dietary niacin intake and chronic kidney disease among adults in the USA: a cross-sectional study - Qishu Li; Wei Lan (Renal Failure)
Background Chronic kidney disease (CKD), which has become a global public health issue, is associated with mitochondrial dysfunction. Niacin is a necessary coenzyme for mitochondrial energy metabolism. However, the association between dietary niacin intake and CKD remains uncertain. This study aimed to investigate the association between dietary niacin intake and CKD in American adults.Methods This is a cross-sectional study. 25,608 individuals aged ≥20 years from the National Health and Nutrition Examination Survey from 2007 to 2018 were involved.Dietary niacin intake was estimated based on 24-hour dietary recalls conducted by trained personnel. CKD was determined by an estimated glomerular filtration rate (eGFR) (<60 ml/min/1.73 m2) or a urinary albumin-to-creatinine ratio (ACR) (≥30mg/g). The association between dietary niacin intake and CKD was investigated using multivariable logistic regression analysis.Results Of 25,608 participants, 17.14% (4388/25,608) had CKD. Compared to individuals with lower niacin intake (quartile [Q]1, ≤15.30 mg/day), those with higher niacin intake in Q2 (15.31–22.07 mg/day), Q3 (22.08–31.09 mg/day), and Q4 (≥31.10 mg/day) exhibited adjusted odds ratios for CKD of 0.89 (95% confidence interval [CI]:0.81–0.99, p = 0.024), 0.83 (95% CI:0.75–0 .92, p < 0 .001), and 0.83 (95% CI:0.75–0.93, p = 0.001) respectively. The relationship between dietary niacin intake and CKD among U.S. adults follows an L-shaped pattern, with an inflection point at approximately 28.04 mg/day.Conclusions These results suggest an L-shaped association between dietary niacin intake and CKD. Individuals with low dietary niacin intake levels should be alert to the risk of CKD.